Planʺ Zapadnago Berega Onezhskago ozera, otʺ Sukhago-Nosa do mai︠a︡ka Kulikova po opisi 1874, 78-80 g.g. (na dvukhʺ) : List 1-yĭ otʺ Sukhago-Nosa / Kopirovali khimicheskoi︠u︡ tushʹi︠u︡ P. Anisimovʺ - Russia. Gidrograficheskīĭ departament (Sankt-Peterburg : Morskoe ministerstvo, Gidrograficheskīĭ departament; [Санкт-Петербург] : Морское министерство, Гидрографическій департамент, 1883)
Plan of the western coast of Lake Onega, from Cape Sukhoy-Nos to the Kulikov Lighthouse, according to the surveys of 1874, 1878-1880, in two sheets. Sheet 1: Cape Sukhoy-Nos to the Kuk River.; Relief shown by hachures and spot heights. Depths shown by soundings and isolines.; Pulkovo meridian.; "I︠U︡go zapadnoĭ chasti Onezhskago ozera." [South western part of Lake Onega] -- across top margin.; "Masshtabʺ 300 sazh. vʺ di︠u︡ĭmi︠e︡." [Scale 300 sazhens in 1 inch].; "No. 177" -- handwritten bottom right margin Grayscale; 1:25,200